The Influence of Work Discipline and Work Facilities on Employee Performance with Job Satisfaction as an Intervening Variable at the Regional Development Planning, Research, and Development Agency of Pematangsiantar City - Amelia Apriyanti Br. Haloho; Calen Calen; Richard Berlien (CV. ADMITECH SOLUTIONS, 2026)
Employee performance is one of the important factors in supporting the success of an organization. Every government agency needs employees with good performance so that organizational goals can be achieved effectively. To realize optimal performance, work discipline, adequate work facilities, and employee job satisfaction are needed. This study aims to test and analyze the work discipline and work facilities that affect employee performance with job satisfaction as an intervening variable at the office of the Regional Planning, Research and Development Agency of Pematangsiantar City. The method used in this study is a quantitative method. The population used in this study is all employees at the office of the Regional Planning, Research and Development Agency of Pematangsiantar City which is 49 people who work in all departments. The data analysis technique was carried out using path analysis. The results of the study show that work discipline has a positive and significant effect on employee performance, work facilities have a positive and significant effect on employee performance, work discipline and work facilities have a positive and significant effect on job satisfaction. Job satisfaction cannot mediate between work discipline and work facilities on employee performance at the Regional Planning, Research and Development Agency of Pematangsiantar City, Data processing using the SPSS 22 application.